Acute comparative effect of foam rolling and static stretching on range of motion in rowers - Penichet-Tomas, A.; Pueo, B.; Abad-Lopez, M.; Jimenez-Olmedo, J. M. (Sustainability, 2021)
Rowers` anthropometric characteristics and flexibility are fundamental to increase stroke amplitude and optimize power transfer. The aim of the present study was to analyze the effect of foam rolling and static stretching on the range of motion over time. Eight university rowers (24.8 ± 3.4 yrs., height 182.3 ± 6.5 cm, body mass 79.3 ± 4.6 kg) participated in an alternating treatment design study with two-way repeated measures ANOVA. The sit and reach test was used to measure the range of motion. Both in the foam rolling and in the static stretching method, a pre-test (T0), a post-test (T1), and a post-15-min test (T2) were performed. A significant effect was observed on the range of motion over time (p < 0.001), but not for time x method interaction (p = 0.680). Significant differences were found between T0 and T1 with foam rolling and static stretching (p < 0.001, d = 0.4); p < 0.001, d = 0.6). The differences between T0 and T2 were also significant with both methods (p = 0.001, d = 0.4; p < 0.001, d = 0.4). However, no significant difference was observed between T1 and T2 (p = 1.000, d = 0.1; p = 0.089, d = 0.2). Foam roller and static stretching seem to be effective methods to improve the range of motion but there seems to be no differences between them.